Humanization of care from the perspective of nurses in a neonatal unit - Tavares, Rosangela Cunha Machado; Reis, Danielle Bonotto Cabral; Camargo, Fatima Cristina Mattara de; Tavares, Tainan Maria Cruz Lopes; Vieira, Claudia Cristina Augusto Rodrigues; Menaguali, Richely Ritta; Olivo, Katlen Susane da Silva (Seven Editora, 2023)
humanization can be understood as an initiative that values the excellence of care. In what tends to the care of newborns, the neonatal units have as main objective to provide continuous resources, prioritizing the best practices, proposing individualized strategies, respecting the particularities and needs of each one. Thus, combining the humanized personality with the actions of health professionals. Objectives:  to describe the profile of nurses working in a neonatal unit; to analyze the humanized practices performed in a neonatal unit; and to discuss the nurses' view of neonatal humanization. Methodology: descriptive, exploratory research with a qualitative approach, carried out in a national health institute. Operationalized through a form and semi-structured interview. Results:  the humanization strategies most cited by the interviewees were the issue of family inclusion in care, the baby's warmth and non-nutritive sucking. Conclusion: a team with varying degrees of understanding on the subject was perceived. In addition to a difficulty, some professionals have difficulty in establishing an interface between theory and practice, limiting the use of humanization tools. There was also a great reference to the insertion of the family in care as a strategy, in addition to the overvaluation of the mother-baby relationship to the detriment of the paternal one, evidencing the need for appropriation of the theme by the nurses, for a better application. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-024